Green synthesis of silver nanoparticles through reduction with Solanum xanthocarpum L. berry extract: characterization, antimicrobial and urease inhibitory activities against Helicobacter pylori - Amin, Muhammad; Anwar, Farooq; Janjua, Muhammad Ramzan Saeed Ashraf; Iqbal, Muhammad Awais; Rashid, Umer (MDPI AG, 2012)
A green synthesis route for the production of silver nanoparticles using methanol extract from Solanum xanthocarpum berry (SXE) is reported in the present investigation. Silver nanoparticles (AgNps), having a surface plasmon resonance (SPR) band centered at 406 nm, were synthesized by reacting SXE (as capping as well as reducing agent) with AgNO3 during a 25 min process at 45 °C. The synthesized AgNps were characterized using UV–Visible spectrophotometry, powdered X-ray diffraction, and transmission electron microscopy (TEM). The results showed that the time of reaction, temperature and volume ratio of SXE to AgNO3 could accelerate the reduction rate of Ag+ and affect the AgNps size and shape. The nanoparticles were found to be about 10 nm in size, mono-dispersed in nature, and spherical in shape. In vitro anti-Helicobacter pylori activity of synthesized AgNps was tested against 34 clinical isolates and two reference strains of Helicobacter pylori by the agar dilution method and compared with AgNO3 and four standard drugs, namely amoxicillin (AMX), clarithromycin (CLA), metronidazole (MNZ) and tetracycline (TET), being used in anti-H. pylori therapy. Typical AgNps sample (S1) effectively inhibited the growth of H. pylori, indicating a stronger anti-H. pylori activity than that of AgNO3 or MNZ, being almost equally potent to TET and less potent than AMX and CLA. AgNps under study were found to be equally efficient against the antibiotic-resistant and antibiotic-susceptible strains of H. pylori. Besides, in the H. pylori urease inhibitory assay, S1 also exhibited a significant inhibition. Lineweaver-Burk plots revealed that the mechanism of inhibition was noncompetitive.